Oral health experiences of individuals with Rett syndrome: a retrospective study - Y.Y.L. Lai; K. Wong; N. M. King; J. Downs; H. Leonard (BMC, 2018)
Abstract Background There is relatively little literature on the oral health experiences of individuals with Rett syndrome. This study described the incidence of dental extractions and restorations in a population-based cohort, according to a range of demographic and clinical factors. The association between bruxism and age was also investigated. Methods Existing questionnaire data in the population-based Australian Rett Syndrome Database for the years 2004, 2006, 2009 or 2011 on genetically confirmed female cases (n = 242) were analysed. Results The incidence rate of restorations and extractions were 6.8 per 100 person years (py) and 9.3 per 100 py respectively. The incidence of extractions decreased with increasing levels of income. Compared to those with a C-terminal mutation, the incidence rate of extraction was higher for those with large deletions (Incidence Rate Ratio (IRR) 4.93; 95% CI 1.46-16.7, p = 0.01). There was a 5% decrease in the risk of frequent bruxism for every one-year increase in age (Risk Ratio 0.95; 95% CI 0.94-0.97). Conclusions Social advantage may provide some protection for dental health in individuals with Rett syndrome. Those with more severe genotypes seemed to have poorer oral health outcomes.